2018
DOI: 10.15761/crr.1000146
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of liver-cancer discovered from the male patients crude serum without depletion of high abundance proteins

Abstract: High abundance proteins (HAP) were often removed from crude serum sample when finding biomarkers of diagnosing cancers, however, it will surely filtrate many potential biomarkers bound to HAP. In order to enable the detection of these potential biomarkers, saving the HAP will be of great significance for finding more biomarkers. Here, a serum proteomics technology was developed for finding biomarkers of liver-cancer from crude human serum without depletion of HAP. The crude human serum (CHS) was dispersed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…They suggested that at exposure to high doses of MTBE, kidney toxicity evolved into nephrocarcinogenesis, suggesting the related role of alpha-2 microglobulin as a biomarker. Luo et al [10] found some potential cancer biomarkers for MTBE-induced liver cancer; these biomarkers were separated from 800 protein spots on a 2D-PAGE gel from human sera. Moreover, lymphoimmunoblastic lymphoma in the lungs, leukemias, astrocytomas, and Leydig cell adenomas were described in rats exposed to MTBE [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that at exposure to high doses of MTBE, kidney toxicity evolved into nephrocarcinogenesis, suggesting the related role of alpha-2 microglobulin as a biomarker. Luo et al [10] found some potential cancer biomarkers for MTBE-induced liver cancer; these biomarkers were separated from 800 protein spots on a 2D-PAGE gel from human sera. Moreover, lymphoimmunoblastic lymphoma in the lungs, leukemias, astrocytomas, and Leydig cell adenomas were described in rats exposed to MTBE [6].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to developing cancer biomarkers, Lou et al [10] recognized an exceptional metabolic biomarker, N-acetylaspartate (NAA) in patients with lung cancer, which is present in inconspicuous levels in normal lung cells. Lou et al [10] developed a sensitive NAA blood assay and found that elevated levels of NAA were detected in the blood, where it was detected as a metabolite in patients with lung cancer in comparison with the levels in age-matched healthy controls. Other studies indicated a close relationship between MTBE and malignancies in laboratory animals [16].…”
Section: Introductionmentioning
confidence: 99%